Prolidase deficiency breaks tolerance to lupus‐associated antigens. (14th December 2013) - Kurien, Biji T.; D'Sousa, Anil; Bruner, Benjamin F.; Gross, Timothy; James, Judith A.; Targoff, Ira N.; Maier‐Moore, Jacen S.; Harley, Isaac T. W.; Wang, Heng; Hal Scofield, R.
Abstract: Aim: Prolidase deficiency is a rare autosomal recessive disease in which one of the last steps of collagen metabolism, cleavage of proline‐containing dipeptides, is impaired. Only about 93 patients have been reported with about 10% also having systemic lupus erythematosus (SLE). Methods: We studied a large extended Amish pedigree with four prolidase deficiency patients and three heterozygous individuals for lupus‐associated autoimmunity. Eight unaffected Amish children served as normal controls. Prolidase genetics and enzyme activity were confirmed. Antinuclear antibodies (ANA) were determined using indirect immunofluorescence and antibodies against extractable nuclear antigens were determined by various methods, including double immunodiffusion, immunoprecipitation and multiplex bead assay. Serum C1q levels were determined by enzyme‐linked immunosorbent assay. Results: Two of the four homozygous prolidase deficiency subjects had a positive ANA. One had anti‐double‐stranded DNA, while another had precipitating anti‐Ro. By the simultaneous microbead assay, three of the four had anti‐Sm and anti‐chromatin. One of the three heterozygous subjects had a positive ANA and immunoprecipitation of a 75 000 molecular weight protein. The unaffected controls had normal prolidase activity and were negative for autoantibodies. Conclusions: Prolidase deficiency may be associated with the loss of immune tolerance to lupus‐associated autoantigens even without clinical SLE.